Current diagnostic strategies for dilated cardiomyopathy: a comparison of imaging techniques. (2nd January 2019) - Porcari, Aldostefano; De Angelis, Giulia; Romani, Simona; Paldino, Alessia; Artico, Jessica; Cannatà, Antonio; Gentile, Piero; Pinamonti, Bruno; Merlo, Marco; Sinagra, Gianfranco
ABSTRACT: Introduction : Dilated cardiomyopathy (DCM) is generally thought as a final common pathway of several conditions leading to the same clinical phenotype. Multiple imaging modalities play a fundamental role in recognizing the underlying pathological substrate in DCM. Areas covered : Echocardiography represents the first reliable and easily accessible diagnostic tool, allowing the identification of associated cardiac abnormalities, such as valve disease and highlighting features associated with an adverse prognosis. Recent advances in technology such as strain analysis and 3D-echocardiography have improved the diagnostic and prognostic capabilities of this technique. Cardiac magnetic resonance (CMR) is considered the gold standard for an accurate and reproducible assessment of ventricular volumes and ejection fraction. In addition, CMR allows us to perform tissue characterization that, through new sophisticated sequences, could be obtained even without gadolinium. Nuclear images could be useful to identify specific causes of left ventricular dysfunction, such as cardiac sarcoidosis and amyloidosis. Finally, endomyocardial biopsy is generally performed if acute myocarditis is suspected in high-risk patients. Expert commentary : Strengths and limitations are different for every method, but multiparametric evaluation of patients and family members could progressively improve current understanding of the disease. This is fundamental to specifically target therapy, allowing us to improve patients' prognosis.